ANALISIS STRUKTUR MODAL DAN LOAN TO DEPOSIT RATIO UNTUK MENILAI KINERJA KEUANGAN LPD DESA ADAT LEMUKIH - Ni Made Wulan Sari Sanjaya (ARTHA SATYA DHARMA, 2017)
This research aim to determine the financial performance Lembaga Perkreditan Desa (LPD) Desa Adat Lemukih seen from the Capital Structure and Loan To Deposit Ratio. Data collection techniques used in this study is in the form of documentation by viewing and recording quantitative data sourced from LPD financial statements. Data analysis technique used in this research is descriptive quantitative. The result of the analysis concludes that LPD Indigenous Financial Performance of Lembaga Perkreditan Desa (LPD) Desa Adat Lemukih is categorized as unfavorable in relation to the result of the three dominant analysis that is not good value is seen from the capital structure proxied by Profitability ratio analysis that is the return on equity ratio (ROE) is good value and the Leverage ratio debt to equity ratio (DER) and loan to deposit ratio (LDR) are not good.